Gender Awareness in The Cambridge Global English Coursebook 8 Grades: A Discourse Analysis - Anjani, Ayu Fitri; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (English Education: Jurnal Tadris Bahasa Inggris, 2022)
Many people are still struggling to cope with gender equality in all aspects of life. There is hope for a balanced role for men and women to participate in any industry. The gender balance today seems to be that both men and women have equal possibilities to present, attend classes, work, and take part in other positive activities. Above and beyond, gender equality can be introduced at a young age by bringing up the roles of men and women in a balanced way of contributing to daily activities, as demonstrated in coursebooks. The excellent coursebook should illustrate the way men and women interact in society based on their roles, position, surroundings, culture, and community structures that are portrayed throughout the form of images and sentence descriptions in a balanced way. However, the current English coursebook with an Indonesian setting has not been able to fulfill gender equality. At this point, the researchers conducted a study to look into various aspects of gender awareness in the Cambridge Global English Coursebook 8 Grades. This study employs qualitative research using content analysis. The data of this study was derived from the content of Cambridge Global English Coursebook 8 Grades, which depicts gender relations. The content was categorized into visibility, jobs, games, household duties, and the data, consisting of pictures and texts from the coursebook. The data of this study was obtained through document analysis. This study showed gender awareness in Cambridge Global English Coursebook 8 Grades. The data were presented as follows: a) There were 113 men and 45 women in the visibility aspects b) There were 17 men and 9 women in the job aspects c) There were 27 men and 10 women in the games or sports aspects d) There were three men and 0 woman in the household duties aspect. Based on the findings, gender stereotypes still exist in the Cambridge Global English Coursebook 8 Grades.